Law's trials : the performance of legal institutions in the US "War on Terror" - Abel, Richard L. (Cambridge, UK : Cambridge University Press, 2018)
'The'War on Terror', which the US launched after the 9/11 attacks, profoundly challenged the rule of law during the 16 years of the Bush and Obama administrations. In the companion volume,'Law's Wars', I defined the rule of law, explained its importance, and charted its fate across five contested terrains : Abu Ghraib, Guantamo Bay, interrogation and torture, electronic surveillance, and battlefield law of war crimes. I focused on the roles of two state institutions (executive and legislature) and civil society (media, lawyers, and NGOs) in defending the rule of law. Because the judiciary claims to be independent and apolitical, it is seen as the ultimate bulwark of the rule of law. The present volume, therefore, deals exclusively with judicial proceedings. Chapter One draws on history, primarily US and especially in moments of crisis, to derive research questions about when and how courts successfully defend the rule of law. The book then discusses six legal processes : criminal prosecutions of accused terrorists; courts martial of military service members for law of war violations; military commissions for Guantamo prisoners, especially the so-called High Value Detainees; habeas corpus petitions by Guantamo detainees (and a few others); civil damage actions by (and compensation schemes for) victims of both the'War on Terror' and terrorism; and civil liberties violations and responses to Islamophobia. The concluding chapter compares the fate of the rule of law across these six domains, as well as with the contested terrains examined in'Law's Wars'. Although the two volumes address some of the same issues, they contain almost no overlap and can be read separately'--
Judging the judges -- Criminal prosecutions -- Courts-martial -- Military commissions -- Habeas corpus -- Civil liberties -- Reversible error?.
Includes bibliographical references and index.
Keywords: Terrorism -- Prevention -- Law and legislation -- United States; Rule of law -- United States; Civil rights -- United States; Prisoners of war -- Civil rights -- Cuba -- Guantanamo Bay Naval Base; Detention of persons -- United States; Habeas corpus -- United States; War on Terrorism, 2001-2009.